Stratigraphy of the Upper Cenomanian-Lower Turonian Chalk succession at Eastbourne, Sussex, UK: Ammonites, inoceramid bivalves and stable carbon isotopes - Gale, A; Kennedy, W; Voigt, S; Walaszczyk, I (2005)
Thirty-one ammonite, and eight inoceramid bivalve taxa are recorded from the Cenomanian-Turonian boundary interval at Eastbourne, Sussex, in southern England, and correlated with the δ13C isotope record in carbonate and organic carbon. New ammonite records from Western Europe include the North American species Cunningtoniceras arizonense Kirkland and Cobban, 1986, Tarrantoceras (Sumitomoceras) conlini Wright and Kennedy, 1981, Puebloites corrugatus (Stanton, 1894) and Euomphaloceras costatum Cobban, Hook and Kennedy, 1989. The ammonites allow definition of three Late Cenomanian (C. guerangeri, M. geslinianum, N. juddii) and three Turonian (W. devonense, F. catinus, M. nodosoides) zones. The inoceramid study enables recognition of the Mytiloides puebloensis Zone, and allows us to demonstrate the absence of the Mytiloides hattini Zone at Eastbourne. The first occurrence of M. puebloensis Walaszczyk and Cobban, 2000, is coincident with that of the ammonite genus Watinoceras, as in the United States Western Interior, and allows precise placement of the Cenomanian-Turonian boundary in the Anglo-Paris Basin for the first time. We present stable carbon isotope data through the succession, including the first δ13 Corg record for the UK Chalk. The positive Cenomanian-Turonian boundary carbon isotope excursion at Eastbourne is reflected in the δ13Ccarb record by an overall stepwise increase in values, whereas the δ13 Corg record displays distinct minima at times of δ13Ccarb plateaux. Each plateau precedes the following δ13C increase recorded in both the carbonate and the organic carbon curves. The distinct pattern in the organic and carbonate δ13C records results in three intervals that show marked increases in the isotopic fractionation between organic and inorganic carbon. We use a combination of carbon isotope, ammonite and inoceramid data to develop a detailed correlation with the proposed C-T stratotype at Pueblo, Colorado, which has a resolution close to that of Milankovitch precession cycles. © 2005 Elsevier Ltd. All rights reserved.